Water quality of Krueng Balee in Lafarge Cement Indonesia Factory in Lhoknga Aceh Besar according to benthos biodiversity - . Wardiah; M. Ali Sarong; Asiah M.D.; Samsul Kamal (Syiah Kuala University, 2012)
The study of the quality of water of Krueng (River) Bale in Factory Environment Lafarge Cement Indonesia (LCI) in Lhoknga Aceh Besar according to benthos biodiversity was aimed to determine the species of benthos and water quality of Krueng Bale according to benthos diversity. The study area was divided into four locations that were the upstream of the tunnel (Location 1), bridge area at the south (Location 2), branch of the river area (Location 3), and the downstream of the two creeks. The study was done from April to June 2012. The method was survey and destructive sampling. The species of benthos was analysed descriptivelly and the diversity was analysed by diversity index formula (H). The results showed that there were 20 species of benthos found in the area and the index of diversity was between 1.996 and 2.652. In brief, River Bale is still suitable as the habitat of aquatic organisms.